Repellent voids for improving geographical routing efficiency in wireless sensor networks. (1st January 2013) - Aissani, Mohamed; Bouznad, S.; Allia, S.E.; Hariza, A.
The geographical routing suffers from communication voids in wireless sensor networks (WSNs). Thus, several void-handling techniques are proposed in the literature, but they are limited in case of critical applications. In this paper, we propose an efficient approach handling both open and closed voids by using three complementary mechanisms. The first mechanism orients each packet that arrives on the network boundary toward the network middle by using the shortest path leading to the sink. The second mechanism is used by a node located on the boundary of a closed void to orient the received packets in optimal paths toward the sink. The third mechanism uses repellent forces generated by each closed void to repulse the packets from its boundary. To discharge the boundary nodes, our approach defines an announcement zone around each closed void and uses a two-hop forwarding mode in each boundary node. Our proposals achieved good performance.